A Contrived Countryside - Hoggart, Keith. author. aut Link
XXVII, 555 p. 9 illus.
Keywords: This book shows how governance regimes before the 1970s suppressed rural prospects of housing improvement and created conditions for middle-class capture. Using original archival sources to reveal the intricacies of local and national policy processes, weak rural housing performances are shown to owe more to national governance regimes than local under-performance. Looking `behind the scenes' at policy processes highlights neglected principles in national governance, and shows how investigating rural housing is fundamental to understanding the national scene. With original insights and a new analytical perspective, this volume offers evidence and conclusions that challenge mainstream assumptions in public policy, housing, rural studies and planning.